THE EFFECT OF SCREWANGEL AND COMMODITIES TO PERFORMANCE OF SCREWCONVEYOR ON TWO VARIATIONS ANGULAR SPEED - Imanda, Jordhy (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
The aims of this research were to make and test the material transportation device of grains dan legumes(corn, soybean, and green beans) screw type (screw conveyor), to find the effect of screw angle (α) andcommodities to performance of screw conveyor, and to find out the best screw angle (α) and commodity toperformance of screw conveyor for each angular speed those are 40 and 54 rpm. This research has beenconducted on December 2014 until February 2015. This research was conducted in two phases, those arecreating device which conducted in CV WIDODO, Kuripan village, West Teluk Betung sub-distric, BandarLampung and testing was conducted at the Laboratory of Power and Agricultural Machinery, AgriculturalEngineering Department, Faculty of Agriculture, University of Lampung. This research was conducted inthree different screw angles, those are 30°, 45°, dan 60°. Later, these three different screw angles is subjectedto three repetitions and in two different angular speed (rpm), those are 40 rpmand 54 rpm. The results showthat the best working capacity of screw conveyor on the variation of screw angle and commodities for eachangular speed for 40 rpm on soybean and 30° screw angle is about 178,6 g/s, while for 54 rpm on greenbeans and 30° screw angle is about 238 g/s. It can be indicate that speed rotation (rpm) and screw angelaffect significantly on screw conveyor;s working capacity.Keywords : Screw conveyor, screw angel, grains and legumes